A Conceptual Framework for Investigating ‘Capture’ in Corporate Sustainability Reporting Assurance - Smith, John; Haniffa, Ros; Fairbrass, Jenny (2011)
The assurance of corporate sustainability reporting has long been a controversial field. Corporate management and assurance providers are routinely accused of ‘capturing’ what should be an exercise in public accountability. This article responds to recent calls for an analysis of the process by which ‘capture’ takes place. Integrating elements of neo-institutional theory and the arena concept, the article sets out a fresh conceptual framework for investigating the dynamics of the interactions between the various bodies active in the assurance field in the UK.
Keywords: arena concept; neo-institutional theory; Conceptual Framework; capture; Sustainability reporting; Assurance